The beneficial effect of fermented Spirulina platensis on reducing oxidative stress in patients with type 2 diabetes mellitus: Fermented Spirulina, a super functional food - Ghafari Ashtiani, Aida; Sharifan, Anousheh; Gharibi, Morteza; Moradzadeh, Rahmatollah (Cellular and Molecular Biology, 2024)
Oxidative stress caused by hyperglycemia can lead to the intensification of hyperglycemia and an increased risk of diabetes complications. Spirulina platensis is a potent free-radical scavenger; it has the potential to be used as a substrate for fermentation by lactic acid bacteria. This study aimed to formulate two functional foods with antioxidant capacity (yogurt containing S. platensis powder / fermented S. platensis powder) for Type 2 Diabetes Mellitus (T2DM) patients and compare the antioxidant effects in diabetic subjects. In this article, for the first time, the antioxidant effect of fermented and non-fermented Spirulina was compared in a clinical study in 'T2DM' patients. By blood sampling, clinical parameters such as FBS, GSH, FRAP, MDA, and CRP before and after each treatment were measured and results were compared between two groups of intervention. Both products as functional foods have a positive effect on the health of diabetic patients by reducing FBS and increasing total antioxidant capacity, and this positive effect is more obvious when yogurt contains fermented lactic acid S. platensis is consumed by T2DM patients.